Projections for Sámi in Norway: Schools as Key to Revitalization - Vangsnes, Øystein Alexander (Nordlyd, 2022)
The paper presents three different projections of the future number of Sámi language users in Norway based on the contemporary number of children receiving instruction in Sámi in the Norwegian school system, either North, Lule or South Sámi. There exist three different curricula for the subject Sámi, one for first language pupils (Sámi 1), one for second language pupils (Sámi 2), and one for pupils with no previous knowledge of the language (Sámi 3). Depending on whether only Sámi 1 pupils become future language users, or also Sámi 2 or even Sámi 3 pupils do so, a sober, moderate, and optimistic prognosis can be made, respectively. The sober prognosis predicts a dramatic decrease for North Sámi and slight decrease for the other two varieties, whereas the moderate prognosis predicts stability for North Sámi and increase for Lule and South Sámi, and the optimistic prognosis predicts an increase for all three varieties. A number of factors that are likely to modulate the prognoses are brought to attention and discussed, unveiling that more information is needed regarding a number of issues that bear on how the future of the Sámi languages in Norway can be estimated.